Study on Alternative Therapeutic Agents on Methicillin-Resistant Staphylococcus Aureus from Clinical and Environmental Isolates (Medical Forum Monthly, 2024)
Introduction: The in vitro antimicrobial activity of Sea buckthorn (SBT) (Hippophaerhamnoides), Green tea (Camellia sinensis) and Dandasa (Juglansregia) on selected methicillin resistant Staphylococcus aureus (MRSA) isolates from clinical samples was tested. The in vitro antimicrobial activity of six antiseptics/disinfectants against MRSA isolated from environmental samples was also evaluated.Study Design: Experimental Observational.Place and Duration of study: This study was conducted in Immunology and Infectious Diseases Research Laboratory (IIDRL) Lab, University of Karachi from January 2011 to July 2011. Materials and Methods: Minimum Inhibitory Concentration (MICs) of plant extracts was determined by micro-broth dilution method and, susceptibility of MRSA isolates from environmental samples against antiseptics/ disinfectants was estimated by the agar disk diffusion and agar well diffusion methods.Results: None of the plant extracts inhibited the isolates originating from blood samples. SBT offered comparatively more inhibitory zones and among the antiseptics/disinfectants, savlon was the most effective.Conclusions: In view of the rising antibiotic resistance, exploring possible natural plant extracts for their antimicrobial action seems like an attractive substitute. The results showed some degree of susceptibility and can be suggested for use in vivoafter standard clinical trials.